Genetics tools for corpora allata specific gene expression in Aedes aegypti mosquitoes - Nouzova, Marcela; Edwards, Marten J; DeGennaro, Matthew; Leyva, Dennys; Tose, Lilian V; Fernandez-Lima, Francisco; Noriega, Fernando G (Scientific reports, 2022)
Juvenile hormone (JH) is synthesized by the corpora allata (CA) and controls development and reproduction in insects. Therefore, achieving tissue-specific expression of transgenes in the CA would be beneficial for mosquito research and control. Different CA promoters have been used to drive transgene expression in Drosophila, but mosquito CA-specific promoters have not been identified. Using the CRISPR/Cas9 system, we integrated transgenes encoding the reporter green fluorescent protein (GFP) close to the transcription start site of juvenile hormone acid methyl transferase (JHAMT), a locus encoding a JH biosynthetic enzyme, specifically and highly expressed in the CA of Aedes aegypti mosquitoes. Transgenic individuals showed specific GFP expression in the CA but failed to reproduce the full pattern of jhamt spatiotemporal expression. In addition, we created GeneSwitch driver and responder mosquito lines expressing an inducible fluorescent marker, enabling the temporal regulation of the transgene via the presence or absence of an inducer drug. The use of the GeneSwitch system has not previously been reported in mosquitoes and provides a new inducible binary system that can control transgene expression in Aedes aegypti.
Keywords: exprese genu; Gene Expression; Drosophila; zvířata; juvenilní hormony; Aedes; Corpora Allata; Juvenile Hormones; geneticky modifikovaná zvířata; Green Fluorescent Proteins; Animals, Genetically Modified; zelené fluorescenční proteiny; corpora allata; Animals